Entrepreneurship and its Impact for Economic Growth - Snitka, Valentinas; Gerdvila, Stasys (Ekonomika, 2001)
In this paper there is taking a closer look at bow the figure of the entrepreneur and entrepreneurship are treated in economic theory. Entrepreneurship is seen by many authors as a very important economic phenomenon. This due to, among other considerations, the possibility that economic growth can be enhanced, employment opportunities created through encouragement of entrepreneurship and self-employment. The research has taken a new direction, bringing out the separate and distinct function of the entrepreneur in contrast to that of the manager. A great deal of emphasis is placed on this difference, because entrepreneurship bas a quality of its own. The essence of entrepreneurship is being different: while manager must operate under normal conditions and in routine business, a successful entrepreneurship requires exactly the opposite qualities.Astonishingly in Lithuania, in the literature on economics the entrepreneur and entrepreneurship has been largely left out. The paper emphasize successful implementation of entrepreneurship development strategy into the Lithuanian economy is the key to business growth that would build extra job places and would be a considerable support of enhancing the country’s economic activity.